THE HISTOLOGICAL AND HISTOCHEMICAL STRUCTURE OF ILEUM IN THE SLENDER-BILLED GULL (Chroicocephalus genei) - Taha, A. M.; Abed, A. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to identify the histological and histochemical composition of the Ileum in the Slender-billed gull (Chroicocephalus genei). It was using histological stains and histological chemical techniques. The results showed that the Ileum was relatively long, so it characterized into two parts: an anterior part and a posterior part. The results showed that the mucous layer in the two parts consisted of villi that appeared conical in the anterior region and conical to a triangle in the posterior part, and the villi were more numerous and longer in the anterior part. The villi covered with a simple columnar epithelial tissue containing goblet cells in the two regions, but the goblet cells were significantly more numerous in the posterior part. The secretory units of Lieberkuhkn's crypts were more widespread and numbered in the posterior part. Clusters of lymphocytes also seemed close to the lymph nodule in the anterior part. The outer muscle layer consisting of one layer of smooth circular muscles appeared in the anterior part, while it was composed of three secondary layers in the posterior part. Histochemically, the two parts of Ileum showed different responses between them for PAS, AB, TB, BP and SB techniques. The study concluded that the histological and histochemical composition of the Ileum appeared somewhat complicated to suit the nature of the food of this bird.